2019
DOI: 10.1021/acs.langmuir.9b00661
|View full text |Cite
|
Sign up to set email alerts
|

DNA Binding to Gold Nanoparticles through the Prism of Molecular Selection: Sequence–Affinity Relation

Abstract: Native DNA strongly adsorbs to citrate-coated gold nanoparticles (AuNPs). The resulting composites (DNA/AuNPs) are valuable materials in many fields, especially in biomedicine. For this reason, the process of adsorption is a focus for intensive research. In this work, DNA adsorption to gold nanoparticles was studied using a molecular selection procedure followed by high-throughput DNA sequencing. The chemically synthesized DNA library containing a central N 26 randomized fragment was sieved through four cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…It turned out that heterogeneous G, T and A-rich sequences are mainly selected, while C-rich ONs disappear from the original randomized DNA pool. These results are in line with the well-known range representing the rising affinity of nucleotides to the gold carrier C < T < A < G [ 21 ].…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…It turned out that heterogeneous G, T and A-rich sequences are mainly selected, while C-rich ONs disappear from the original randomized DNA pool. These results are in line with the well-known range representing the rising affinity of nucleotides to the gold carrier C < T < A < G [ 21 ].…”
Section: Introductionsupporting
confidence: 88%
“…Our previous studies revealed that incubation conditions, length and composition of ONs influence the kinetics and affinity of their non-covalent adsorption to GNPs surface [ 17 ]. In this study, mixtures of GNPs and all the above-listed ONs were incubated under the same conditions, which provided effective non-covalent adsorption of ONs to the surface of GNPs (17.3 ± 2.1 nm in diameter, DLS data) [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aptamer selection was performed for AuNP targets using normal or A-rich random ssDNA libraries in two separate screening sessions under otherwise identical selection conditions. Notably, multiple unrelated studies have evaluated binding of one or more particular ssDNA sequences (e.g., polyadenine) to planar gold surfaces and gold nanoparticles. The choice of employing an A-rich library is based on a prior study that indicated both adenine-rich ssDNA and pure polyadenine induce aggregation of gold nanoparticles during their seeded growth as evidenced by a redshift and overall broadening in the characteristic extinction peak . As detailed previously above, the key differences between the CompELS approach used in the current work and the widely used SELEX process for the selection of aptamers stems from the elimination of intermittent oligonucleotide elution (i.e., intentional dissociation of all target–oligonucleotide complexes each screening round) and amplification (i.e., PCR-based sequence enrichment each screening round) steps during each selection round.…”
Section: Results and Discussionmentioning
confidence: 99%